KEADILAN GENDER DALAM RANAH KEPEMIMPINAN MUHAMMADIYAH (Studi Terhadap Struktur Kepengurusan di IMM Sleman Yogyakarta) - Muhammad Ridha Basri (Universitas Muhammadiyah Surakarta, 2014)
Muhammadiyah is a movement that introduced himself as a reform movement. One of which contains an autonomous organization since 1917 is Aisyiyah, as a representation of women in particular. This became evident that Muhammadiyah upholds degrees women and put them in strategic positions. In the long run, Muhammadiyah through the Legal Affairs Committee and Tajdid trying to rise decisions and edicts in favor of gender equality. Among them, women are allowed to go into politics and become involved in the leadership structure. Not only in the political field iconic public sphere, women are also allowed to lead in the realm of worship to become a priest prayer for the men in particular contekt. Essential staple of gender justice can be understood by the majority of cadres, especially in the PC. IMM Sleman period 2014-2015.